Handbook of modern management in Philippine local government - Sajo, Tomas Alejan; Joaquin, Ma Ernita T.; Santiago, Eden V.; University of the Philippines (Diliman). Center for Local and Regional Governance ([Quezon City] Center for Local and Regional Governance, National College of Public Administration and Governance, University of the Philippines, 1998)
Purpose: A guide to the processes and key elements involving local/government management.
Content/s: organizational Development. Human Resource Management. Internal control. Management. Culture. Work process.
Jointly published with Public Administration Promotion Centre, German Foundation for International Development.
Keywords: Local government -- Management -- Philippines -- Handbooks, manuals, etc; Public administration -- Philippines -- Handbooks, manuals, etc